Open source machine translation with DELPH-IN - Bond, Francis (2011)
The Deep Linguistic Processing with HPSG Initiative (DELPH-IN) provides the infrastructure needed to produce open-source semantic transfer-based machine translation systems. We have made available a prototype Japanese-English machine translation system built from existing resources include parser, generators, bidirectional grammars and a transfer engine.